(untitled) (Journal of Academic Research, 2021)
This paper aims to account a comprehensive study on the effect of Fused Deposition Modelling (FDM) parameters towards impact strength of Polypropylene/Ultra-High Molecular Weight Polyethylene (PP/UHMWPE) (90/10) composite using Fractal Factorial Design (FFD). The current study converged the investigation on five parameters namely; layer thickness (LT), number of shells (NOS), extrusion temperature (T), raster angle (RA), and infill speed (IS). The impact strength samples were manufactured according to the FFD recommended runs, which take two levels for every parameter into account. Scanning electron microscope (SEM) analysis was done to explore the effect of parameters setting on the samples’ microstructure and insight on the correlation between samples’ impact strength and parameters setting. The outcomes from the experiment revealed a significant effect for all investigated parameters but in various levels including some of the 2-factor interactions. Layer thickness has dominating effect as compared to single effect parameters, followed by infill speed. Layer thickness and number of shells interaction has the highest effect of all the parameters interactions. The best parameters setting has improved the impact strength of PP/UHMWPE composite by 61.5% compared with the worst setting results. Output of this study provides distinct insight into the effect of FDM parameters on the impact strength of PP/UHMWPE (90/10) composite. SEM investigation revealed the details behind altering the impact strength as result of process parameters changing.